Challenging Locard’s Exchange Principle: Knowing Former Postulates of Forensic Science to Overhaul the Fundamentals - Shweta Sharma (Indian Journal of Forensic Medicine and Pathology, 2025)
Fundamental principles of forensic science have one of the most popular of these the exchange principle by Edmund Locard. Locard’s exchange principle is summed up in a statement as “Every contact leaves a trace”. In practical case scenarios it has been observed that such exchange of evidences might not occur at all in a perfectly committed crime. Since, the origins of Forensic Science were not supported by the larger scientific communities due to its indecisive nature. The fundamentals of any discipline of science have a lot of importance in its development in the long years. There has been no mathematical or statistical explanation for Locard’s exchange principle and thus, the reliability of the same has been always questioned. Some studies have suggested likelihood ratio or Bayes factor to support the exchange principle. While few suggest modification of the statement to bring clarity of this principle. It is necessary to match the criteria required for a statement to become a scientific principle with reference to Locard’s principle. The current article is an effort to measure the validity of Locard’s principle including its merit/demerits and encourage the scientific community for complying to standards and corrections required for wider application in field of criminal investigation